A meta-analysis on the effects of probiotics on the performance of pre-weaning dairy calves - Liyun Wang; Honghong Sun; Haixu Gao; Yaohui Xia; Linsen Zan; Chunping Zhao (Journal of Animal Science and Biotechnology, 2023)
Abstract Background Probiotics have been used in livestock production for many years, but information on their benefits during the early life of calves is inconsistent. This study aimed to assess the effects of probiotics on the performance of pre-weaning dairy calves and identify the factors influencing their effect sizes. Results Forty-nine studies were selected for meta-analysis based on the inclusion and exclusion criteria. The study qualities were evaluated using a predefined risk assessment tool following GRADE guidelines. Meta-analysis results showed that probiotics increased the growth performance (body weight by 1.988 kg and average daily gain by 40.689 g/d), decreased digestibility and feed efficiency (feed conversion rate by 0.073), altered rumen parameter (decreased acetate by 2.815 mmol/L and increased butyrate by 0.788 mmol/L), altered blood parameter (decreased AST by 4.188 U/L, increased BHBA by 0.029 mmol/L and IgG by 0.698 g/L), increased faecal parameter (faecal bacteria counts by 0.680 log10 CFU/g), based on the strict criteria (P SMD < 0.05, I 2  < 50%). Additionally, probiotics increased digestibility and feed efficiency (starter dry matter intake by 0.034 kg/d and total dry matter intake by 0.020 kg/d), altered blood parameter (increased IgA by 0.313 g/L, IgM by 0.262 g/L, and total antioxidant capacity by 0.441 U/mL, decreased MDA by 0.404 nmol/mL), decreased faecal parameter (faecal score by 0.052), based on the loose criteria (P SMD < 0.05, I 2  > 50%). Regression and sub-group analyses showed that probiotic strains, supplementation dosage, and methods significantly affected the performance of calves. The probiotics supplied with more than 9.5 log10 CFU/d significantly increased IgA and IgM contents (P SMD < 0.05). Additionally, the compound probiotics significantly increased TDMI, IgA, and IgM (P SMD ≤ 0.001). Furthermore, probiotics supplemented in liquid (whole milk or milk replacer) significantly increased TDMI and decreased faecal score (P SMD < 0.05), while in whole milk, they significantly increased body weight, IgA, and IgM (P SMD < 0.001). Conclusions Probiotics could improve the growth performance, feed intake and efficiency, rumen fermentation, immune and antioxidant capacity, and health of pre-weaning calves. However, the effect sizes were related to the dosage, composition, and supplementation methods of probiotics.